Activation of the nickel foam as a current collector for application in supercapacitors - Kovalenko, Vadym; Kotok, Valerii; Kovalenko, Igor (Eastern-European Journal of Enterprise Technologies, 2018)
Nickel foam is widely used as a current collector and as a major component of the faradic electrode in supercapacitors. Activation of nickel foam would allow increasing the capacity of the nickel hydroxide electrode or preparing high-speed electrodes without additional active material. Multiple (1 – 20 times) short-term (5 min) treatment in a 1 М solution of HCl, H3BO3 or H2C2O4 has been proposed. The possibilities of activation of commercial nickel foam samples manufactured by “Novoment-Perm” (Russian Federation) and “Linyi Gelon LIB Co Ltd” (China) have been studied. Activated and non-activated nickel foam samples have been studied by means of X-ray diffraction analysis and scanning electron microscopy, electrochemical characteristics were determined by means of cyclic voltamperometry and galvanostatic charge-discharge cycling in the supercapacitor regime. The comparative analysis of nickel foam samples from Chinese and Russain manufacturers has revealed very low reactivity and low susceptibility to activation of nickel foam from Chinese manufacturer. An assumption has been made that low reactivity is because the sample is composed of Ni-P or Ni-B alloy. The maximum specific capacity of 0.084 F/cm2 has been obtained after 20 treatments in HCl solutions. The activation mechanism is the increase in the specific surface area of nickel. However, this value is significantly lower than that of non-activated nickel foam from Russian manufacturer (0.333 F/cm2). It has been discovered that the nickel foam sample from Russian manufacturer can be easily activated. The maximum activation effect is achieved when treated with oxalic acid: specific capacities are 1.213 F/cm2 (one treatment), 6.578 F/cm2 (five treatments) and 20.003 F/cm2 (twenty treatments). The activation mechanism is the formation of nickel oxalate on the surface of nickel foam. The results of the comparative analysis have revealed the effectiveness of activation of the nickel foam sample from Russian manufacturer by multiple short-term treatment with oxalic acid. It has been concluded that activation of the nickel foam sample from Chinese manufacturer by multiple short-term treatment in solutions of hydrochloric, boric and oxalic acids is ineffective. Activation of nickel foam from Chinese manufacturer requires the development of a different method.